Power of many: Assessing the economic impact of the global fiscal stimulus - Carlos De Resende; René Lalonde; Stephen Snudden (Bank of Canada, 2010)
The Bank of Canada Global Economy Model (BoC-GEM) is used to examine the effect of various types of discretionary fiscal policies on different regions of the globe. The BoC-GEM is a microfounded dynamic stochastic general-equilibrium global model with six regions, multiple sectors, and international linkages. The authors use the model to assess four main fiscal policy concerns: (i) how the effect of an isolated local fiscal stimulus differs from one jointly implemented in all regions; (ii) which regions are most likely to gain from joint fiscal stimuli, and why; (iii) how the impact of fiscal stimulus can differ conditional on how it is implemented, its timing and duration, and its magnitude relative to that of other regions; and (iv) how the impact of fiscal policy is affected by the inability of monetary policy to push nominal interest rates below zero. The authors use their results to gauge the potential effect of fiscal policy initiatives of the G-20 countries in 2009 and 2010.
Keywords: E52; E58; E61; E63; F42; 330; Business fluctuations and cycles; Fiscal policy; International topics; Recent economic and financial developments; Konjunkturpolitik; Finanzpolitik; Diskretionäre Politik; Geldpolitik; Wirtschaftswachstum; Wirtschaftsmodell; Welt